Revisiting Causes of Firm Exit for Divestiture Spin-Off in the Last Five Years: A Systematic Literature Review - Adriana, Dadi; Hartoyo, Hartoyo; Syarief, Rizal; Anggraeni, Elisa (Aptisi Transactions On Technopreneurship (ATT), 2024)
This study revisits and analyzes the causes leading to firm exit in divestiture spin-offs over the past five years, aiming to consolidate findings from recent literature and uncover evolving trends. Using a systematic literature review of Scopus publications from 2019 to 2024 and employing the PRISMA methodology, this study analyzed a final sample of 97 journal articles to examine the key factors influencing divestiture spin-offs. The results identify four primary causes for divestiture spin-offs: market periphery and overlap, asset redeployment, unprofitable resource utilization, and the critical timing decision between redeployment and divestiture. These insights reveal a significant shift in research focus, offering valuable knowledge for executives and management to move beyond traditional views and understand the underlying causes in a more nuanced way. This study provides essential guidance for executives, firm management, and policymakers, supporting informed decision-making in business unit divestitures and contributing to a more sustainable economic cycle. The originality and value of this research lie in its comprehensive identification of the causes behind firm exit in divestiture spin-offs, laying a robust foundation for future research and practical applications.